Long-term outcomes and associated factors among intensive care unit survivors in a lowincome country: a multicenter prospective cohort study - Matovu, Ham Wasswa; Luggya, Tonny Stone; Mukiza, Nelson; Agaba, Peter Kaahwa (BMC Research Notes, 2024)
Post-ICU survivors face higher mortality and often require costly rehabilitation or palliative care, such as occupational therapy, physiotherapy and hospice. However, there is a lack of data quantifying the demand for these services, particularly in developing countries like Uganda. Therefore, this prospective cohort study aimed to investigate the 90-day mortality rate, functional status, and mortality risk factors among 121 ICU patients discharged from three tertiary hospital ICUs in Uganda by tracking their vital and physical functional status for three months with follow-ups on days 30, 60, and 90, and identifying risk factors through Cox regression.